SOSIALISASI PENGEMBANGAN PROTOTYPE COMPANY PROFILE BERBASIS WEBSITE UMKM PENGUSAHA GERABAH DAN KERAMIK PAGERJURANG MELIKAN BAYAT – WEDI KLATEN - Maria Atik Sunarti Ekowati; Kristyana Dananti; Sri Wening (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2023)
The rapid development of Information Technology encourages Pagerjurang- Melikan MSME residents to always develop creations and have creativity in achieving maximum results in all fields. The need for easy, fast and timely information has become a way of life for humans, in the current 4.0 to 5.0 era. The rapid business competition forced the owners of the Pagerjurang - Melikan pottery craftsmen to find the right media to sell their products and innovate to develop more attractive and highly marketable types and forms of products. Purpose of Outreach Socialization Development of Website-Based Prototype Company Profile Umkm Pottery and Ceramic Entrepreneurs Pagerjurang Melikan Bayat – Wedi Klaten. Website is an internet application that can be accessed by almost all people today. The purpose of implementing PkM activities is to design and develop a website-based prototype company profile for Umkm Pottery and Ceramic Entrepreneurs Pagerjurang Melikan Bayat – Wedi Klaten. Because the sales made by MSMEs are still traditional, although there are some who have used the WA group and Facebook, but have never used a website application. The company profile prototype development method is waterfall, namely through several stages starting from planning and data collection, system design with Data Flow Diagrams (DFD), Entity Relationship Diagrams (ERD), programming in PHPMySQL and XAMPP languages. Results of the Company Profile Website for UMKM Pottery Pager Jurang - Melikan Pay -Wedi Klaten, Outcome of implementing the Website which is expected to help provide solutions to problems encountered during the process carried out by UMKM manually.